Bronchioloalveolar Carcinoma Mimicking as Pneumonia: A Case Report - Bhavesh Patel; Cheguri Vasavi; Arti Dhawal Shah; Chirag Chakravarti; Anchal Jain (Journal of Clinical and Diagnostic Research, 2023)
Bronchioloalveolar Carcinoma (BAC) also known as alveolar cell carcinoma is a subtype of adenocarcinoma that is more common in women and non smokers. It accounts for almost 5% of all lung cancers. Bronchioloalveolar carcinoma may appear as a wide variety ranging from solitary nodule to patchy, lobar or multilobar opacities. The mucinous, non mucinous, ambiguous or mixed are the histological types of BAC. The mucinous variety of BAC sometimes may present as a consolidation which is indistinguishable from an infective pneumonia on a radiological picture. Hereby, authors present a case of 65-year-old male patient, who was evaluated for non resolving pneumonia for a time span of one year. He presented to the Respiratory Medicine Outpatient Department with a cough and expectoration for the past nine months. Antibiotic courses did not provide the patient any sort of relief and there was no change in the size of the lesion. Chest X-ray has shown right sided non homogenous opacity and later Contrast Enhanced Computerised Tomography (CECT) thorax and biopsy (computed tomography-guided) was done from the same site for further evaluation. Cytology done from CT-guided biopsy sample showed typical lepidic growth pattern. Histopathologically, it showed mucinous variety of BAC. Usually, the patients have no symptoms but an abnormal chest X-ray, while a few have features like coughing with expectoration and pain in the chest. Only cytology or biopsy can help with a proper diagnosis, which can be done via needle biopsy (CT or fluoroscopy guided) or transbronchial biopsy and Bronchoalveolar Lavage (BAL). It has rarely been documented in the literature that BAC masquerades as a consolidation with very little change.